A clinical and echocardiographic study of patients with the hypermobility syndrome. Issue 6 (December 1981) - Grahame, R; Edwards, J C; Pitcher, D; Gabell, A; Harvey, W
Abstract : Three age- and symptom-matched groups of patients with a hypermobility score of 5-9, 3-4, and 0-2 (controls), respectively, were examined for clinical and echocardiographic evidence of mitral valve prolapse and other stigmata of a collagen disorder. Mitral valve prolapse, a reduced upper segment/lower segment mitral ratio, reduced skin thickness, spinal anomalies, and a history of fracture were found to be significantly commoner among the hypermobile patients than the controls. The data suggest that the so-called hypermobility syndrome, far from being a benign locomotor disorder of healthy persons, may be a forme fruste of a hereditary disorder of connective tissue.